Consumer Legal Awareness In Purchasing Hard Medicine Without A Doctor's Prescription (Study at Pharmacies in Kramat Jati District, East Jakarta City) - Andra Maula Aditya Andra (Faculty of Law, Universitas Negeri Semarang, 2024)
ABSTRACT. Hard drugs are drugs that must be used or with a doctor's prescription, but in practice, consumers still often buy hard drugs without a doctor's prescription, even though from the consumer's perspective, the consumer's obligation is to read or follow information instructions and procedures for the use or utilization of goods and/or services. , for security and safety. Authorized institutions or governments such as BPOM must take part in preventing and enforcing the distribution of hard drugs without a doctor's prescription with more thorough outreach and supervision, because basically, it is stipulated in existing regulations that BPOM has pre-market and post-market functions. The results of the discussion revealed that the stage of consumer legal awareness in Kramat Jati District, East Jakarta, only reached stage 2 (two), which is why consumers still buy hard drugs without a doctor's prescription is due to a lack of legal understanding. For BPOM, although there have been many efforts made to increase legal awareness, in carrying out its functions, BPOM is still not in accordance with the principles of consistency, efficiency and proportionality in CROB which makes the law ineffective. Therefore, consumers should fulfill their obligations in accordance with the UUPK, and the Government should implement good preventive methods to increase consumers' legal awareness, one way is by implementing the nudging concept in the KIE program as a strategic effort to increase consumers' legal awareness of purchasing hard drugs without a prescription. doctor.